Critical success factors in knowledge management: a case study based on the implementation of a knowledge academy - Onofre, Inês Vieira Oliveira (2022)
Nowadays, knowledge is considered a key resource for organizations, crucial for obtaining long-term sustainable competitive. In line with this principle, many organizations are making efforts toward the implementation of knowledge management (KM) initiatives, recognizing that their competitive foundation lies in the effective way to capture, retain, store and share knowledge. Thus, this research aims to understand how organizations can implement KM initiatives, with a comprehensive study to identify critical success factors, and based on a practical project to implement a knowledge academy in a multinational organization. In order to achieve this objective, the adopted methodology in this research first went through a systematic literature review in order to identify the critical success factors with most influence on the implementation of KM practices. Then, based on the results found with this theoretical approach, it was possible to identify and analyse, in a practical context within a multinational company, the critical factors that contributed the most to the success of a knowledge academy implementation, a project in which the author of this study was involved. The results found suggest that factors related to the organization and people, such as the definition of a clear strategy, the definition of performance measures to evaluate and monitor the strategy, the involvement of top management, or even the organizational culture itself, represent some of the factors that have the most influence on the successful implementation of KM initiatives. With this research, it is expected to contribute from a theoretical perspective to the KM area through the compilation, categorization and classification of a set of critical success factors reported in the literature and subsequently analyzed and validated in a practical context. From a practical perspective, it is expected that these results can contribute as a consultative tool to support the preparation of strategies in this area by organizations wishing to implement KM initiatives.